Adsorção de íons metálicos de efluente aquoso usando bagaço do pedúnculo de caju: estudo de batelada e coluna de leito fixo - Moreira, Sarah de Abreu (2008)
Recently, the use of agroindustry residues (pure or chemically modified) for metal removal from industrial effluents offers a potential alternative to existing treatment technologies. The agrowastes are most studied because are readily available, cheap, biodegradable, sludge free and of low cost and land investment. In this work was used the cashew (Anacardium occidentale L.) peduncle bagasse as adsorbent for metal removal from aqueous solution and wastewater aqueous from electroplating industries local (Fortaleza, Ceara-Brazil). Adsorption systems in batch and fixed bed column were studied. Previously was investigated the chemical treatment, the particle size effect, adsorbent concentration and pH effect. The results showed that the treatment employed in the cashew peduncle bagasse with 0.1M NaOH for 3 h was the most efficient. The material characteristics: used on metal adsorption were: particle size ranged 20 – 59 mesh, adsorbent concentration (50g/L) at pH 5.0. The kinetic study indicated that the adsorption equilibrium multielementary were achieved in 60 minutes (pH 5.0) and followed a pseudo-second order model. The adsorption capacity of cashew peduncle bagasse for heavy metals had been evaluated using Langmuir and Freundlich adsorption isotherms. The Langmuir’s model gave best results for all metal ions in a multielementary system. In the second step of the work were carried out experiments to optimization of the column operational parameters. The results showed that for a flow rate of 3.0 mL/min and bed height of 12.0 cm there is an increased on the metal removal. The breakthrough curves for multielementary system indicated the order for adsorption capacity: Pb+2 > Cu+2 > Ni+2 > Zn+2 > Cd+2. The column parameters obtained with the synthetic effluents were applied in a real sample contained Cu+2, Ni+2 and Zn+2. It was found to be an efficient for the removal of Ni+2 and Zn+2. The metal desorption on the column was efficient using 1.0 M HCl as eluent. The tests of recycling of the column showed that the adsorbent can be used only for a cycle.